The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.femsle.2004.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the murine cecal microbiota as revealed by terminal restriction fragment length polymorphism and 16S rRNA gene clone libraries

Abstract: The maturation of murine cecal microbiota was determined by terminal restriction fragment polymorphism (T-RFLP) and 16S rRNA gene clone libraries. Cecal microbiota in specific pathogen free (SPF) mice aged four to 10 weeks were collected. The cluster of samples in 4-week-old mice was different from those of other ages based on T-RFLP profiles. The majority of clones obtained in this study belonged to the Clostridium coccoides (C. coccoides) group, the Bacteroides group or the Lactobacillus group. Phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…A detailed view into the colonisation process during mouse development highlights that microbial composition is not only influenced by genotype, but also by stage of development. Previous studies based on fingerprinting approaches found that the caecal microbiota in SPF mice changes drastically with age, but stabilises after 4 weeks 45. In our study based on 16S rRNA gene clone libraries, the microbial community continued to change after week 4b, fluctuating in the proportions of the three most abundant phyla ( Firmicutes , Bacteroidetes and Proteobacteria ; figure 1B) until 10 weeks of age, at which point stable Firmicutes -dominated communities became apparent.…”
Section: Discussionsupporting
confidence: 59%
“…A detailed view into the colonisation process during mouse development highlights that microbial composition is not only influenced by genotype, but also by stage of development. Previous studies based on fingerprinting approaches found that the caecal microbiota in SPF mice changes drastically with age, but stabilises after 4 weeks 45. In our study based on 16S rRNA gene clone libraries, the microbial community continued to change after week 4b, fluctuating in the proportions of the three most abundant phyla ( Firmicutes , Bacteroidetes and Proteobacteria ; figure 1B) until 10 weeks of age, at which point stable Firmicutes -dominated communities became apparent.…”
Section: Discussionsupporting
confidence: 59%
“…Sequencing of 2 primary targets within bacterial 16S rRNA genes yielded valuable compositional data pertaining to the human fecal microbiome of 242 healthy adults ( 6, 7 ) . In the Human Microbiome Project, 18 different body sites were sampled and sequenced.…”
Section: The Human Gut Microbiome: the Toolkit Behind The Sciencementioning
confidence: 99%
“…Previously published studies demonstrated the variation in composition of the gut microbiome among locations within the gastrointestinal tract in different mammalian species. For example, 16S rRNA gene sequencing has been deployed to study the maturation of murine cecal microbiota, and these studies demonstrated the existence of a large number of yet-unidentified bacteria that inhabit the mammalian intestine ( 6 ) . Such sequencing strategies, which are culture independent, are essential for determining bacterial composition of the microbiome and its relative stability and diversity over time.…”
Section: The Human Gut Microbiome: the Toolkit Behind The Sciencementioning
confidence: 99%
“…Polymerase chain reaction (PCR) amplification was performed as described by Kibe et al [21]. Two pairs of primers were used: 27f (5 0 -AGAGTTTGATCCTGGCT-CAG-3 0 ) and 1492r (5 0 -GGTTACCTTGTTACGACTT-3 0 ) as the universal primer, and 27f and Lab-677r (5 0 -CAC-CGCTACACATGGAG-3 0 ) as the specific primer set for lactic acid bacteria (LAB) designed by Heilig et al [22].…”
Section: Pcr and T-rflp Analysismentioning
confidence: 99%